Facial Expression Recognition Based on Texture Features - Najeb, Alaa Nabeel Haj; Nasser, Nasser (Al-Nahrain Journal for Engineering Sciences, 2021)
Facial expressions are a form of non-verbal communication, they appear as changes on the surface of the facial skin according to one’s inner emotional states, aims, or social communications. Classification of these expressions is a normal process for humans, but it is a challenging task for machines.Lately, interest in facial expression recognition has grown, and many systems have been developed to classify expressions from facial images. Any expression recognition system is comprised of three steps. The first one is face acquisition, then feature extraction, and finally classification. The classification accuracy depends primarily on the feature extraction step. Therefore, in this research we study many texture feature extraction descriptors and compare their results under the same preprocessing circumstances; moreover, we propose two improvements for one of these descriptors, which give better results than the original one. We validate the results on two commonly used databases for expression recognition using Matlab programming language, wishing all of that to be an interesting point for researchers in this field.